Accuracy Required in Measurements of Refractive Index and Hygroscopic Response to Reduce Uncertainties in Estimates of Aerosol Radiative Forcing Efficiency. Issue 12 (16th June 2018) - Valenzuela, Antonio; Reid, Jonathan P.; Bzdek, Bryan R.; Orr‐Ewing, Andrew J.
Abstract: The magnitude of aerosol radiative forcing resulting from the scattering and absorption of radiation is still uncertain. Sources of uncertainty include the physical and optical properties of aerosol, reflected in uncertainties in real and imaginary refractive indices ( n and k ) and relative humidity (RH). The effect of RH on the geometrical size of aerosol particles is often reported as a hygroscopic kappa parameter (κ). The objective of this study is to explore the sensitivity of radiative forcing efficiency (RFE) to changes in particle properties in order to better define the accuracy with which optical and hygroscopic measurements must be made to reduce uncertainties in RFE. Parameterizations of precise values of n and k are considered as functions of RH for ammonium sulfate (AS) and brown carbon (BrC). The range of the RFE estimated for typical uncertainties of n and κ for AS of 0.1 μm dry radius is less than ±7% and is not affected by an increase of RH. For typical sizes of AS in the atmosphere (0.35 μm dry radius), the range of the RFE increases to ±20% at 90% RH and ±15% at 99% RH. Absorbing small BrC particles (0.1 μm dry radius) cause cooling at the top of the atmosphere, and as RH and κ increase, the RFE is more negative compared to the usual assumptions of dry unhygroscopic BrC. For larger BrC particles (0.35 μm dry radius), the change in RFE for RHs ~100% compared to dry conditions can take values around −100%. Key Points: More precise data set of refractive indices for nonabsorbing aerosol than previously used in other studies are retrieved from BB‐CRDS It is possible to provide more accurate RFE values using refined optical and microphysical properties from CRDS measurements The first time the sensitivity of the radiative forcing efficiency to uncertainties in the complex refractive index and the hygroscopic response is evaluated